(untitled) (Sustainability in Debate, 2024)
This article aims to analyze the dynamics of the socio-biodiversity of the Caatinga region in the hinterlands of Sergipe, foreseeing the context of fragmentation of the biome, but also the transmission and emergence of ecological, socioeconomic and cultural practices that contribute to the conservation of this patrimony. As a spatial area, municipalities in the hinterlands of Sergipe were delimited. The methodology is based on carrying out theoretical, literature and field research, as well as semi-structured interviews and the formation of focus groups between researchers and the subjects who carry out the Caatinga maintenance strategies. The results of this study point to the predatory advance of the destruction of the associated biome, especially for the expansion of agricultural activities. However, in contrast to this scenario, experiences, knowledge and practices legitimized by social groups and traditional peoples that contribute to the construction of socio-biodiversity emerge and are consolidated.